Evaluasi Klinikopatologis Karsinoma Sel Skuamosa yang Berkembang dari Ulkus Marjolin - Kharisma, Anggie; Susilo, Hery; Retnani, Diah (RSUD Dr. Saiful Anwar Province of East Java, 2021)
Introduction: Marjolin's ulcer is a malignant process in the skin caused by trauma or chronic inflammation. This malignancy is rare and aggressive. Squamous cell carcinoma (SCC) is the most common manifestation of burns. Case Illustration: A 51-year-old woman came to Saiful Anwar Hospital Malang with a complaint of a cauliflower-like lump on the upper arm of her right hand since 8 months ago. The lump was initially as small as a fingertip (1cm), then it got bigger. The patient suffered burns on his body after being hit by gasoline spray 33 years ago. The patient also complains of a painful sensation and a foul odor in the area of ​​the lump. Conclusion: The inflammatory process has an essential role in the development of Marjolin's ulcer.